Soil Properties Prediction and Assessment Using Geographic Information Systems (GIS) and Analytic Hierarchy Process (AHP) - ابراهيم أمجد; توفيق فياض; مهند مهنا (Latakia University Journal -Engineering Sciences Series, 2023)
Geographic information systems is an effective tool for displaying and analyzing spatial data, and has shown a very important role in various aspects of geotechnical engineering, including the preliminary investigation stage. This study aims to achieve integration between geotechnical investigations and geographic information systems (GIS) to predict soil properties in unexplored places, as this was applied in the study area, which is (Aleddikhar square) in Latakia city, with a total area estimated at (115) acres, and the number of bores is (45) to enter data into the (GIS) environment and (5) bores to calibrate the results. The Inverse Distance Weighted method was adopted as a mathematical statistical method for predicting data in unexplored locations. The accuracy of the work was (87.72%) by comparing the data resulting from the maps of the five bores with the real data of those bores. With the aim of evaluating the study area according to the tested parameters and soil properties, a map was developed using the Analytic Hierarchy Process, based on GIS, and by studying four factors: (soil classification, natural land slope, ground water level and swelling potential). Note that the study area was divided into three categories according to its building suitability.